1881 Ill. Pub. Laws 71 §1 - (:unkn) unknown (General Publisher, 1881)
Prohibited the possession, sale, giving, loaning, or bartering any slung-shot, metallic knuckles, or other deadly weapon. Violators guilty of a misdemeanor, fined not less than ten but no more than two hundred dollars.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION